PENGARUH BEBAN KERJA, STRES KERJA, DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA BANK RAKYAT INDONESIA (BRI) CABANG KEBAYORAN BARU - Adelia Fitriana, (2022)
This quantitative research has the aim of testing and knowing "The Influence of Workload, Job Stress, and Job Satisfaction on Work Productivity at Bank Rakyat Indonesia (BRI) Kebayoran Baru Branch". Respondents used in the study amounted to 90 respondents who were employees of the BRI branch of Kebayoran Baru. The analysis technique in this study is the Coefficient of Determination Test, T Test (Partial) and F Test (Simultaneous) and using the Smart PLS 3.0 software. The results obtained in the test are (1) workload has a significant effect on the work productivity of the Kebayoran Baru branch of BRI (2) work stress has a significant effect on the work productivity of the Kebayoran Baru branch of BRI (3) job satisfaction has a significant effect on the work productivity of the Kebayoran Baru branch of BRI (4) The influence of workload, work stress, and job satisfaction have a significant impact on the work productivity of the BRI Kebayoran Baru branch.